Transcendence and history : the search for ultimacy from ancient societies to postmodernity - Hughes, Glenn, 1951- (Eric Voegelin Institute series in political philosophy., 2003)
"Transcendence and History is an analysis of what philosopher Eric Voegelin described as "the decisive problem of philosophy": the dilemma of the discovery of transcendent meaning and the impact of this discovery on human self-understanding. The explicit recognition and symbolization of transcendent meaning originally occurred in a few advanced civilizations worldwide during the first millennium B.C.E. The world's major religious and wisdom traditions are built upon the recognition of transcendent meaning, and our own cultural and linguistic heritage has long since absorbed the postcosmological division of reality into the two dimensions of "transcendence" and "immanence." But the last three centuries in the West have seen a growing resistance to the idea of transcendent meaning; contemporary and "postmodern" interpretations of the human situation - both popular and intellectual - indicate a widespread eclipse of confidence in the truth of transcendence."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved